HEADACHE--A SINONASAL SYMPTOM AND MORE… A REVIEW ARTICLE - Kaur, and, A; Singh, A (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol 7 No 1 (2013): IJBS Vol.7 No.1 January-June 2013, 2013)
Headaches and facial pain are common complaints.  In many cases, patients are referred to an otolaryngologist to determine if head pain is sinus related.  In the absence of other nasal or sinus symptoms, some rhinogenic headaches can be overlooked or misdiagnosed.  A complete history and thorough ENT examination, including nasal endoscopy with or without coronal CT scans is key to the correct diagnosis. 1 Headache resulting from disease of the nose or paranasal sinuses are usually associated with symptoms (congestion, fullness, discharge, obstruction) that point to the site of origin.  Occasionally, however nasal or sinus disease can be manifested solely as headache.
Keywords: Headache; Sinusitis; FESS.